2021
DOI: 10.1186/s13578-021-00616-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of non-histone protein crotonylation in biomedicine

Abstract: Crotonylation of proteins is a newly found type of post-translational modifications (PTMs) which occurs leadingly on the lysine residue, namely, lysine crotonylation (Kcr). Kcr is conserved and is regulated by a series of enzymes and co-enzymes including lysine crotonyltransferase (writer), lysine decrotonylase (eraser), certain YEATS proteins (reader), and crotonyl-coenzyme A (donor). Histone Kcr has been substantially studied since 2011, but the Kcr of non-histone proteins is just an emerging field since its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 117 publications
2
20
0
Order By: Relevance
“…Its mechanism of action and the acyltransferase and deacyltransferase used are similar to those of acetylation which occurs mainly on the lysine residues of histones [ 1 , 34 , 35 ]. With the development of proteomics and the application of crotonylation labeling technology, crotonyl modifications are found to exist on non-histone proteins as well [ 36 ]. In this study, we focus on the role of non-histone crotonyl modifications in the process of white fat browning in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action and the acyltransferase and deacyltransferase used are similar to those of acetylation which occurs mainly on the lysine residues of histones [ 1 , 34 , 35 ]. With the development of proteomics and the application of crotonylation labeling technology, crotonyl modifications are found to exist on non-histone proteins as well [ 36 ]. In this study, we focus on the role of non-histone crotonyl modifications in the process of white fat browning in mice.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Different from the tissue specific distribution of β-hydroxybutyrylation, crotonylation of nonhistone protein is widely distributed in subcellular compartments and affects diversity of protein function, such as gene transcription, DNA damage response, enzymes regulation and metabolic pathways. 43 Crotonate, mainly produced by the colon microbiota, is the SCFA precursor of crotonyl-CoA. From this aspect, crotonylation can be considered as a link between the host and gut microbiota.…”
Section: Donors Writers Erasers and Readers Of Protein Acylationmentioning
confidence: 99%
“…More studies identified lysine crotonylation (Kcr) in nonhistone proteins (124)(125)(126). Kcr is conserved and regulated by a range of enzymes and coenzymes, including lysine crotonyltransferase (writer), lysine decarboxylase (eraser), certain YEATS proteins (reader), and crotonyl-coenzyme A (donor) (127). It is well known that P53 is a tumor suppressor protein that binds to specific DNA sequences and transcriptionally activates target genes to regulate critical cellular processes, including cell cycle control, apoptosis, and DNA repair under genotoxic stress.…”
Section: Crotonylationmentioning
confidence: 99%